2005
DOI: 10.1007/s00418-005-0070-4
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus

Abstract: We previously identified a tissue-specific gene, short palate, lung, and nasal epithelium clone 1 (SPLUNC1), in nasopharyngeal epithelial tissues. SPLUNC1 was differentially expressed in nasopharyngeal carcinoma. Bioinformatic analysis revealed that SPLUNC1 has the bactericidal permeability-increasing protein/lipid-binding protein (BPI/LBP) domain and a 19 amino acid signal peptide, which suggest that it is a secretory protein. Its precise cellular localization in the respiratory tract is mainly in mucous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…The anatomical distribution of BPIFA1 protein expression in human fetuses is similar to that observed in adults (40). In upper respiratory tract secretions, BPIFA1 can be detected in saliva, nasal lavage fluid, and middle ear effusions (9,14,24,32,34,40,44). In lower respiratory tract secretions, BPIFA1 has been detected in sputum, tracheal secretions, airway lining fluid, and bronchoalveolar lavage fluid (BALF) (9,18,23).…”
Section: Expression and Distributionsupporting
confidence: 58%
See 1 more Smart Citation
“…The anatomical distribution of BPIFA1 protein expression in human fetuses is similar to that observed in adults (40). In upper respiratory tract secretions, BPIFA1 can be detected in saliva, nasal lavage fluid, and middle ear effusions (9,14,24,32,34,40,44). In lower respiratory tract secretions, BPIFA1 has been detected in sputum, tracheal secretions, airway lining fluid, and bronchoalveolar lavage fluid (BALF) (9,18,23).…”
Section: Expression and Distributionsupporting
confidence: 58%
“…BPIFA1 was also detected in the parotid gland and submucosal glands of nasal polyps, tongue, and sinus tissue but not on their surface epithelium (18,19,36,38). The anatomical distribution of BPIFA1 protein expression in human fetuses is similar to that observed in adults (40). In upper respiratory tract secretions, BPIFA1 can be detected in saliva, nasal lavage fluid, and middle ear effusions (9,14,24,32,34,40,44).…”
Section: Expression and Distributionmentioning
confidence: 61%
“…The coding region of the SPLUNC1 gene was inserted into the pEGFP vector as previously described (14). The plasmid p2089 (Maxi-EBV), which contained the complete EBV genome of the B95-8 strain was kindly provided by Professor W. Hammerschmidt (GSF-National Research Center for Environment and Health, Germany).…”
Section: Ethicsmentioning
confidence: 99%
“…SPLUNC1 was predicted to exert host defense functions, based on its sequence homology with other known antimicrobial proteins such as bactericidal permeability increasing protein and LPS-binding protein (LBP) (9). We previously demonstrated that the Th2 cytokine IL-13 significantly reduces SPLUNC1 expression and secretion from well-differentiated human primary airway epithelial cells, rendering a host susceptible to bacterial infections (10).…”
mentioning
confidence: 99%